Upaya Pengembangan Profesi Guru Anak Usia Dini - Nurul Mupida Lubis; Dimas Dwika Syahramanda; Raudhatul Jannah; Hilwa Faza Nabila Bidawi,; Lia Sumayyah; Nanjah Fachira Ayundari; Isnaini Isnaini (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Professionalism itself has not been understood by PAUD because it is not only an intention or desire. His sincerity must be reflected in his actions. PAUD teacher certification provides a positive meaning so that PAUD teachers continue to consistently improve their own professionalism. PGPAUD needs introspection to seek all means to increase the competitiveness of graduates as well as academic products and other services, which are achieved, among others, through improving the quality of education in order to have quality excellence. Keywords: professionalism, teachers, early childhood, Indonesia